STRATEGI PENGEMBANGAN EKONOMI LOKAL KABUPATEN LAMPUNG TIMUR - Bambang Suhada (Derivatif : Jurnal Manajemen, 2017)
The economy of East Lampung Regency in the last five years is still dominated by agriculture, forestry, and fishery sector. The biggest economic sectors contributing to GRDP at current prices for 2014 are agriculture, forestry and fishery sector of 36.61 percent followed by mining and quarrying sector 30.01 percent (primary sector). While the services sector companies 0.08 percent or the lowest of the existing seventeen sectors. The agriculture, forestry, and fishery sectors which are the base sector, its role in encouraging economic growth in East Lampung is not considered as the prime mover sector. The dominance of agriculture, forestry, and fishery sector has not been able to boost the acceleration of growth of other sectors, especially the manufacturing sector, as the resulted commodities have not added value (value added) and have not optimally impacted the improvement of people's welfare.There are three strategic issues that need to get serious attention in the context of local economic development of East Lampung Regency, namely: (i). The weak capacity of local communities to manage their potentials optimally, (ii). The relatively low institutional capacity and managerial organization as a prerequisite for optimizing the management of potential or economic resources and (iii). Not yet developed competitiveness of agricultural commodities (competitive advantage).Some policies needed to encourage economic growth acceleration of East Lampung Regency, namely: (i). The need to revitalize the institutional partnership of integrated agribusiness (integrated partnership) by institutional consolidation at the farmer level to become an independent farmer group with legal status, (ii). Considering that agricultural commodities tend to be perishable, their production is seasonal and therefore requires rapid handling, it is necessary to create added value through agro-industrial processes to become marketable products, and (iii). One of the efforts to reduce or minimize the risk of farming is by introducing agricultural insurance program. Based on Law number 19 of 2013 on protection and empowerment of farmers, the Ministry of Agriculture has established a working group of agricultural insurance, especially in assisting rice farming (AUTP) and cattle (AUTS).Keywords : Local Economic Development, Value Added, Institutional Agribusiness